(untitled) (Baghdad Science Journal, 2016)
The dispersion relation of linear quantum ion acoustic waves is derivate according to a fluid approach that depends on the kinetic description of the systems of charged particles model. We discussed the dispersion relation by changing its parameters and graphically represented. We found through graphs that there is full agreement with previous studies on the subject of interest. That motivates us to discuss the dispersion relation of waves depending on the original basic parameters that implicitly involved in the relationship which change the relationship by one way or another, such as electron Fermi temperature and the density at equilibrium state.